Tata Kelola Data Statistik Menuju Transformasi Statistik dalam Perspektif Collaborative Governance Plus Multi Helix (Studi Pada Badan Pusat Statistik) - Maratis, Jimmy; Fefta Wijaya, Andy; Wike, Wike (Jurnal Ilmiah Administrasi Publik, 2025)
The aim of this research is to explore and analyze statistical data management and identify the role of Multi Helix in the statistical transformation process. This research uses a descriptive qualitative approach with 17 informants. to provide solutions to challenges in overcoming data problems at the national and sub-national levels as well as local government agencies. National Statistics Transformation aims to build national statistical governance and capabilities to produce quality national statistical data. The statistical data governance model used at BPS in managing BPS statistical data uses generic statistical business process model (GSBPM) to obtain quality data. At BPS, quality data and publications create a shared spirit of mutual trust that BPS is able to make publications that can be used by the wider community. Capacity for joint action requires strong understanding and harmonization between stakeholders. actors, as well as close relationships to determine the joint actions needed to achieve the desired goals.